Association of metabolic NCD risk factors with oral, breast and cervical precancers and cancers in India. Issue 4 (30th October 2019) - Kedar, Ashwini; Hariprasad, Roopa; Kumar, Vipin; Dhanasekaran, Kavitha; Mehrotra, Ravi
Abstract : Objective: To find an association between metabolic non-communicable disease (NCD) risk factors (high blood pressure (BP), high random blood sugar (RBS) and overweight /obesity) and oral, breast, cervical cancers/precancerous or potentially malignant conditions. Design: This is an observational study using convenience sampling. The participants were screened through opportunistic or population-based screening. Setting: The study was conducted at a health promotion clinic (HPC) located in Northern India under the Indian Council of Medical Research. HPC is a screening clinic where screening is done for hypertension (HT), diabetes mellitus (DM), obesity, and oral, breast and cervical cancers. The study was conducted between December 2016 and January 2019. Participant: The number of participants screened was 8352 (6712 women and 1640 men). All consenting men and women above 18 years were included. All participants were screened for oral cancer, DM, HT and obesity. All women were also screened for breast and cervical cancers. Cervical screening was done for non-pregnant women 21 years and above with history of sexual activity. Result: Oral potentially malignant disease (OPMD) was the most prevalent, followed by breast cancer, oral cancer, cervical cancer and cervical precancer. High RBS had a strong association with oral cancer (OR=2.29, 95% CI 1.09 to 4.82, p=0.03) and breast cancer (OR=1.95, 95% CI 1.01 to 3.76, p=0.05). High BP had a strong association with breast cancer (OR=2.50, 95% CI 1.43 to 4.35, p<0.0001). An inverse association was noted between oral cancer and overweight/obesity (OR=0.20, 95% CI 0.08 to 0.48, p<0.0001). Current tobacco use was strongly associated with oral cancer (OR=6.51, 95% CI 3.63 to 11.67, p<0.0001) and OPMD (OR=9.82, 95% CI 8.13 to 11.86, p<0.0001). No association was elicited between the metabolic NCD risk factors and cervical cancer/precancer. Conclusions: The study reaffirms that NCD metabolic risk factors determine oral and breast cancers. Besides NCD risk factors, current tobacco use was a strong determinant of OPMD and oral cancer. Hence, primary and primordial prevention measures to control NCD metabolic risk factors and tobacco use should move along with secondary prevention of breast and oral cancers.